ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI SIKAP SKEPTIS KONSUMEN PADA IKLAN HIJAU (STUDI KASUS PADA MASYARAKAT KOTA PALEMBANG KONSUMEN AIR MINUM DALAM KEMASAN (AMDK) MEREK ADES "PILIH, MINUM, REMUKKAN") - Fathiyah, Fenny; Wahab, Zakaria (Journal of Management and Business Review, 2016)
The number of green advertising has been increasing recently accompanied by the increasing number of environmental problems faced. This research aims to determine the influence of environmental concern, buying behavior, and conservation behavior on skepticism toward green advertising. In addition, this research aims to determine whether customers demographic characteristics (age, gender, and education level) moderate the relationship between factors affecting skepticism toward green advertising. The method used in this research is descriptive and associative. Data has been obtained by distributing questionnaires to 100 respondents that are Palembang residents who are buying and consuming Ades Mineral Water at least once in the last 3 months. Accidental sampling method has been selected to obtain data. The techniques of analysis used include multiple linear regression and moderated regression analysis, while for the processing of the data, SPSS 21 for Windows has been used. The results of this research indicate that: (i) environmental concern was 5,8 percent having significant influence on skepticism toward Ades green advertising, (ii) buying behavior was 19,2 percent having significant influence on skepticism toward Ades green advertising, (iii) conservation behavior was 23.6 percent, having significant influence on skepticism toward Ades green advertising, and (iv) customers demographic characteristics by age and gender moderate (strengthen) the relationship between factors affecting skepticism toward Ades green advertising, while level of education not moderate (strengthen) the relationship between factors affecting skepticism toward Ades green advertising.